Combined brachytherapy and external beam radiation: an effective approach for palliation in esophageal cancer - Laskar, Sarbani Ghosh; Lewis, Shirley; Agarwal, Jai Prakash; Mishra, Shagun; Mehta, Shaesta; Patil, Prachi (Journal of Contemporary Brachytherapy, 2015)
Purpose : Palliation of dysphagia is a challenge in advanced esophageal cancer. The addition of external beam radiotherapy (EBRT) to intraluminal brachytherapy (ILBT) has shown significant improvement in dysphagia relief and symptom scores. The aim of the present study was to evaluate the efficacy of combined use of ILBT and EBRT. Material and methods : The medical records of 148 patients with advanced/metastatic esophageal cancer were screened from January 2008 to April 2014, and 74 patients were found eligible for the analysis. All patients received two fractions of 8 Gy each of ILBT, followed by EBRT. Patients were assessed for the symptom scores of dysphagia, odynophagia, regurgitation, and chest pain and weight was recorded periodically. Results : For a median follow-up of 6 months, the median OS was 9.5 months (95% CI: 7.5-10.5). The median dysphagia free survival was 6 months (95% CI: 4.8-7.1). The scores for dysphagia significantly improved after completion of 1st ILBT (p = 0.000), 2nd ILBT (p = 0.000), and at 3 months after EBRT compared to ILBT (p = 0.02). Overall 47% had improvement in dysphagia scores and 35% maintained the improvement of scores till last follow up. There was significant improvement in weight after completion of ILBT (p = 0.001) and at 3 months after completion of EBRT (p = 0.00). Twenty nine (39%) patients required nasogastric (NGT) insertions and 12 (16%) needed hospitalization for supportive care. 36.4% had complications in the form of stricture (27%), fistula (5.4%), and bleeding (4%). Conclusions : Palliative radiotherapy is an effective alternative for palliation of dysphagia with improvement in symptom scores being evident and sustained. The results of this clinical audit were comparable with those from the trial setting.